Genital hygiene behaviors of women and their effect on vaginal infections - Yeşilçiçek Çalık, Kıymet; Erkaya, Reyhan; İnce, Gülnur; Korkmaz Yıldız, Nazende (Marmara University, 2020)
Objectives: This descriptive study was carried out with the purpose of identifying women's genital hygiene behaviors and the effects of these behaviors on vaginal infections.Methods: The study included 266 married women, ages 20-49, who consented to participate in the research and were registered at the University Hospital in Trabzon, Turkey. The data were collected with a questionnaire, the Genital Hygiene Behavior Inventory (GHBI), a gynecological examination and the Pap smear test. The results were evaluated by descriptive statistical methods (frequencies, percentages, means, and standard deviation), the Student's t-test, Kruskal Wallis and Mann Whitney U tests.Results: The mean GHBI score of the women was found to be 77.41 +/- 9.05. There were statistically significant differences in genital hygiene behaviors between the women in terms of the women's education, profession, presence or absence of social security, income, husband's work and education, number of pregnancies, total number of children, spontaneous abortion, presence of vaginal discharge and the duration of complaints (p<0.05). Of the women, 54.9% reported that they had vaginal discharge; 45.1% had pathological vaginal discharge and odor (34.6%) and burning (35%) complaints. The speculum examination showed that 42.6% had pathological discharge and the incidence of genital infection was 79% in the Pap smear. According to the speculum examination, 71.4% of the women were found to have either pathological or non-pathological discharge.Conclusions: It was found that the mean GHBI score of the women was slightly above the moderate level and that wrong and inadequate genital hygiene practices increased the women's risk of vaginal infection.
Keywords: Genital Hygiene; Genital Hygiene Behavior Inventory; Genital Infection; Women